Anomalous ellipticity dependence of the generation of near-threshold harmonics in noble gases - Wang, Bincheng; Zhang, Yinfu; Lan, Pengfei; Zhai, Chunyang; Li, Min; Zhu, Xiaosong; Chen, Jing; Lu, Peixiang; Lin, C. D. (My University, 2021)
We measured the ellipticity dependence of the harmonic yield of He, Ne, Ar, Kr, and Xe. It is found that the harmonic yield in general decreases monotonically with increasing laser ellipticity but anomalous dependence does occur for each atom for some harmonic orders. We found that the degree of anomaly is weakest in helium but is stronger for the heavier atoms. The anomaly also depends on laser intensity. To explain these features, we developed a quantum trajectory Monte Carlo (QTMC) model based on the quantum path integral theory to study high-order harmonic generation (HHG). The model includes the effect of Coulomb potential from the target ion, thus it is capable of calculating near-threshold harmonics quantitatively. This model reveals that the presence of Coulomb potential would generate orbiting trajectories which are responsible for the anomalous ellipticity dependence near the threshold.